Korelasi Antara Loneliness, Self-Harm dan Suicidal Ideation Pada Siswa SMA di Pinggiran Sungai - Fauzi, Zainal; Hayati, Sri Ayatina (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2024)
Early adults experience a transition period from adolescence to adulthood with responsible roles involving themselves in social relationships and exploration. The changes that occur are not only biological but also psychological. Feelings of loneliness can arise because individuals feel dissatisfied with the relationships or social relationships they are currently in. Although not everyone with self-harm behavior will always end up committing suicide, people with this behavior are at risk. Suicide, suicide attempts, self-harm, and suicidal ideation are significant public health problems among the younger generation. This research aims to determine the correlation between loneliness, self-harm and suicidal ideation in high school students who live on the riverbank. This researcher used correlation statistics to test the relationship between Loneliness, Self-Harm and Suicidal Ideation in high school students living in Pinggiran Sungai. Samples were taken using random sampling. This research uses several data analysis techniques. Product moment correlation is used to test the relationship between two variables and multiple regression and ANOVA are used to test hypotheses about the relationship between two or more variables together. Validity in this research is in the form of Pearson Correlation Loneliness validity 0.75, Self-Harm 0.78, Suicidal Ideation 0.80, and reliability in this research is Cronbach's Alpha with reliability loneliness 0.82, self-harm 0.85, Suicidal ideation 0.88This research found a significant relationship between Loneliness (X1) and Self-Harm (X2) with Suicidal Ideation (Y). Loneliness has a greater influence (coefficient 0.414) than Self-Harm (coefficient 0.109). Overall, these two variables are significant in influencing Suicidal Ideation in high school students on the riverbank.